OPCML is a broad tumor suppressor for multiple carcinomas and lymphomas with frequently epigenetic inactivation. - Yan Cui; Ying Ying; Andrew van Hasselt; Ka Man Ng; Jun Yu; Qian Zhang; Jie Jin; Dingxie Liu; Johng S Rhim; Sun Young Rha; Myriam Loyo; Anthony T C Chan; et al. (PLoS ONE)
Background Identification of tumor suppressor genes (TSGs) silenced by CpG methylation uncovers the molecular mechanism of tumorigenesis and potential tumor biomarkers. Loss of heterozygosity at 11q25 is common in multiple tumors including nasopharyngeal carcinoma (NPC). OPCML, located at 11q25, is one of the downregulated genes we identified through digital expression subtraction. Methodology/principal findings Semi-quantitative RT-PCR showed frequent OPCML silencing in NPC and other common tumors, with no homozygous deletion detected by multiplex differential DNA-PCR. Instead, promoter methylation of OPCML was frequently detected in multiple carcinoma cell lines (nasopharyngeal, esophageal, lung, gastric, colon, liver, breast, cervix, prostate), lymphoma cell lines (non-Hodgkin and Hodgkin lymphoma, nasal NK/T-cell lymphoma) and primary tumors, but not in any non-tumor cell line and seldom weakly methylated in normal epithelial tissues. Pharmacological and genetic demethylation restored OPCML expression, indicating a direct epigenetic silencing. We further found that OPCML is stress-responsive, but this response is epigenetically impaired when its promoter becomes methylated. Ecotopic expression of OPCML led to significant inhibition of both anchorage-dependent and -independent growth of carcinoma cells with endogenous silencing. Conclusions/significance Thus, through functional epigenetics, we identified OPCML as a broad tumor suppressor, which is frequently inactivated by methylation in multiple malignancies.